A Semantic Study of the Beautiful Names of Allah and His Supreme Attributes: a Pragmatic Study in the Sahih Al-Bukhari (Raparin Journal of Humanities (RJH), 2024)
the correct understanding of God Almighty is not only the most necessary but the primary prerequisite of religious life, and knowledge of His names and attributes is also connected with this comprehension. Nonetheless, knowledge in this area has never been without significant and stormy adversities whereby many notions related to the names and attributes of God have become displaced and misinterpreted over time. Since Arab accent is crucial in appropriate understanding of these subjects Arabic is thus a powerful and key tool for dealing with these issues. Arabic language is relevant in this study in light of the fact that it is very relevant in crafting right conceptions of the aforementioned concepts. The language’s ignorance has led to many misunderstandings. The research entitled: ‘A Semantics Investigation of the Beautiful Names of Allah and the Supreme Qualities of Allah: A Pragmatic Analysis of Sahih Al Bukhari’. The importance of this issue cannot be overemphasized because it restores the original methodology of the early generations of approaching the understanding of the names and attributes of God. The purpose of this work is to recall the intentions of the first generations in the recognition of God’s names and qualities. I hope that this work helps fulfill the reason for the creation of humanity and jinn, as stated in the Quran: Thus, the Quran says:. existing and based,"Upon the authority of Allah, it stated: “And I did not create the jinn and mankind except to worship Me” Quran 51:56. For this study I carried out a comprehensive study of Sahih Al-Bukhari and its explanations and Arabic dictionaries for all the information on the topic to be sourced. It is made up of two major parts and is followed by the introduction and preface and contains findings from the study. Based on the method used in this piece of research, the analysis is analytical, because it is only possible to choose hadiths that are most discussed in scholarly conversations due to the fact that there is a large number of prophetic hadiths that refer to the names and attributes of Allah.